A multi-omics approach to understand mesenchymal stem cell ageing - Jiang, C (2019)
Mesenchymal stem cell (MSC) ageing is characterised by impaired proliferation and osteoblast differentiation, leading to a reduction in bone mass and bone strength. Recent evidence indicates that transcriptional and epigenetic changes may underlie the impaired MSC functions with age. This thesis aims to systematically characterise the transcriptional and epigenetic changes associated with MSC ageing and to identify candidates for restoring MSC functions. RNA-seq, DNA methylation-array and ATAC-seq were carried out on undifferentiated bone marrow-derived MSCs from young (20 - 29 years) and old (62 – 87 years) donors. The RNA-seq data showed that an increased donor age was associated with significant changes in the expression of lineage determining genes. Moreover, the DNA methylation array and ATAC-seq analysis revealed a less permissible epigenetic state for osteogenesis in the old donors, indicating that a shift in lineage preference was already evident in MSCs prior to differentiation. In order to compare transcriptional changes during osteogenesis between MSCs from young and old donors, RNA-seq time-course experiments consisting of 16 time points were carried out. The expression profiles of a panel of tri-lineage differentiation markers indicated that the old donor MSCs were unable to fully commit towards osteoblast differentiation upon osteogenic induction and were diverted towards an adipogenic fate. The top 3 enriched gene networks amongst the 91 differentially expressed genes were associated with the canonical WNT, JAK/STAT and PPARG pathways. Canonical WNT activation via GSK3B inhibition significantly increased the ALP activity and matrix mineralisation of the old donors. Interestingly, WNT activation shifted the transcriptomic profiles of the old donors towards the young donors, thus further supporting the thesis that the canonical WNT pathway could be a potential target for restoring the osteogenic potential of ageing MSCs. More importantly, this study demonstrates the validity of the concept that a multi-omics approach has a promising potential for identifying therapeutic candidates to restore MSC functions in the elderly.